Attitude and behavior on hotel choice in function of the perception of sustainable practices - Cristóbal Fernández Robin; Jorge Cea Valencia; Geraldine Jamett Muñoz; Paulina Santander Astorga; Diego Yáñez Martínez (Tourism & Management Studies, 2016)
Chile is one of the countries with higher GPB in Latin America and important sources of incomes and employment comes from tourism. Hotels are adopting sustainable practices but it is unknown whether customers value this. This research looks to measure consumer attitude, perception and preference for hotels based on their sustainable practices. A survey was applied to 208 guests at Chilean hotels. Correspondence and exploratory factor analysis was carried. Lack of knowledge about "Sustainability”, but Willingness to pay extra for Sustainable Hotels, indicate a higher level of commitment and care for environment. Three clusters were obtained: ‘non-Committed’, ‘Influenced’ and ‘Committed’.